INFLUENCE OF QUANTITATIVE ALLOYING OF TOOL STEELS FOR HOT DEFORMATION ON THE LEVEL OF HARDENING - V. N. Fedulov (Литьë и металлургия)
The influence of complexly experimental tool steels: C (0,4–0,50%), Si (0,6–1,2%), Mn (0,17–0,8%), Cr (0,8–3%), W (0,9– 4%), Mo (0,01–3.5%) and V (0,28–1,8%) on their ability to hardening due to only high-temperature tempering after induction melting, casting in the ceramic mold and air cooling (without deformation) and after the various modes of complete heat treatment cycle